ANALISIS PENINGKATAN KUALITAS PELAYANAN MENGGUNAKAN METODE SERVICE QUALITY ( SERVQUAL ) (Study Kasus Wisata Pulau Dodola Kabupaten Pulau Mototai) - Umar, Almukmin; Sibua, Amrin; Saleh, Hasrul; Prasetyo, Nurtjahyo Budi; Zulfikram, Zulfikram; Jurtulis, Niga (Journal Industrial Engineering and Management (JUST-ME), 2023)
Dodola Island Tourism is one of the tourist destinations located on Dodola Island, Morotai Island Kabupatean applies two Big Dodola Islands and Little Dodola. This study aims to determine the level of service quality and satisfaction of visitors or tourists in. Then find out how much influence the quality of service consisting of five dimensions, namely Physical Evidence, Reliability, Responsiveness, Assurance, Attention, on tourist satisfaction in Dodola Island Tourism with using Simple service quality (servqual) methods with SPSS tools. Data collection was carried out through literature study, field observation and questionnaire distribution to 25 respondents. The results of this study show that the level of service quality in Dodola Island Tourism is sufficient, while the level of tourist satisfaction is not good, because one dimension, namely Physical Evidence, is included in the category of not good. Therefore, Dodola Island Tourism needs to improve physical evidence is a dimension that has a limited presentation, which is 0.9698. This means that it is in the category of not good and is in the interval range of 0.9671, that is, it is in perception and expectation. Significantly to the satisfaction of tourists on Dodola Island Tourism.